ANALYSIS OF ADOLESCENT DEABILITY IN SUNGAI ITIK VILLAGE, SUNGAI KAKAP, KUBU RAYA DISTRICT - Juniarti, Juniarti; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to determine the forms of juvenile delinquency that occur in the village of Sungai Itik and its factors qualitatively. The research approach used in this research is qualitative research with descriptive research methods. This study analyzes real facts about the factors of juvenile delinquency in Sungai Itik village, Sungai Kakap district, Kubu Raya district. The purpose of this research is to descriptively describe, reveal and present what is according to data, facts and reality about juvenile delinquency in Sungai Itik Village, Sungai Kakap District, Kubu Raya Regency. The results of this study indicate the existence of juvenile delinquency in Sungai Itik Village, Sungai Kakap District, Kubu Raya Regency. Juvenile delinquency that occurred in Sungai Itik Village is divided into 3 types of juvenile delinquency in the form of ordinary delinquency, delinquency that leads to criminal acts and special delinquency. Juvenile delinquency occurs because of the lack of religious education and family factors with the dominant factor being familyfactors that cause damage to the psychological condition of adolescents. Regarding the handling of juvenile delinquency in Sungai Itik Village, it is in the form of coaching and involving teenagers in village activities such as August 17 and community service activities. This is expected to be able to foster a sense of caring for the village and prevent youth from deviant activities and direct them in positive activities.